The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1016/s0168-6496(03)00198-3
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical effects on microbial activity in natural waters: the interaction of reactive oxygen species and dissolved organic matter

Abstract: Bacterial utilization of dissolved organic matter (DOM) in surface waters is closely linked to photochemical transformations of DOM. Photochemically produced reactive oxygen species (ROS) play a central role in many photochemical reactions, but the role of ROS for the photochemical facilitation of bacterial utilization of DOM is previously not known. We exposed lake water with high DOM concentrations to simulated sunlight, with and without the addition of ROS scavengers, and quantified the effect on the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 20 publications
1
72
1
Order By: Relevance
“…Our results conflict with the recent results of Scully et al (2003a), who attempted to study the effect of photoproduced reactive oxygen species on DOM bioavailability. They found that the use of a ROS scavenger (furfuryl alcohol) during sunlight irradiation increased subsequent bacterial growth (measured as cell abundance only) in incubations, relative to samples irradiated without the scavenger.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results conflict with the recent results of Scully et al (2003a), who attempted to study the effect of photoproduced reactive oxygen species on DOM bioavailability. They found that the use of a ROS scavenger (furfuryl alcohol) during sunlight irradiation increased subsequent bacterial growth (measured as cell abundance only) in incubations, relative to samples irradiated without the scavenger.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, Febria et al (2006) found that the production of hydrogen peroxide (H 2 O 2 ) in two delta lakes that were also sampled herein (CON and TK) outpaced the rate of removal during a period of uninterrupted sunshine in 2004, leading to an accumulation of H 2 O 2 within the water columns. Production of ROS during previous studies of DOM photodegradation has been observed to inhibit community-level rates of carbon production (Scully et al 2003;Anesio et al 2005;Glaeser et al 2014) and result in changes in bacterial community composition (Glaeser et al 2010(Glaeser et al , 2014. Further, in a prior study by Lund and Hongve (1994), declines in BA of up to 60% were observed after only an hour when UV-irradiated DOM was mixed with bacteria.…”
Section: Photoreactivity Of Mackenzie River Freshet Dommentioning
confidence: 93%
“…These by-products of the photodegradation process are short-lived, but nevertheless inhibit bacterial growth and production (Lund and Hongve 1994;Henle and Linn 1997;Anesio et al 2005). To some extent, therefore, irradiation of DOM by sunlight simultaneously stimulates and inhibits heterotrophic bacterial production (BP) (Scully et al 2003;Ruiz-Gonzalez et al 2013), leading to complex interactions that can result in enhanced, negative, mixed, or no effect on bacterial community metabolism (Lonborg et al 2016). In addition, the bacterial community composition may be altered either by exposure to ROS (Glaeser et al 2010;Glaeser et al 2014) or in response to the increased lability of the pool of DOM substrate (Judd et al 2007;Piccini et al 2009;Paul et al 2012;Ward et al 2017), giving rise to a species assemblage that is better suited to the ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, CDOM protects the aquatic biota from exposure to UV radiation [2], which can be very significant during summertime in CDOM-poor environments such as mountain lakes located above the tree-line [3]. Another important issue is that radiation absorption by CDOM yields reactive species, such as ‱ OH, 1 O 2 and the triplet states 3 CDOM*, which can be involved into transformation of dissolved compounds, including xenobiotics, as well as into the photoprocessing of CDOM itself [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%